You can kill - Zanetti, Rebecca (Zanetti, Rebecca. Laurel Snow thriller., 2024)
The first body is torn apart, blood and flesh discovered across both state and federal lands. As the victims multiply, a pattern emerges -- each is related to past cases investigated by Laurel Snow, with the assist of Huck Rivers, Washington Fish and Wildlife captain. When friends and loved ones are targeted, things become even more chillingly personal.